How Much Do Side Effects Contribute to Discontinuation? A Longitudinal Study of IUD and Implant Users in Senegal - Chin-Quee, Dawn; Diadhiou, Mohamed; Eichleay, Margaret; Youssef, Ahmed; Chen, Mario; Bernholc, Alissa; Stanback, John (Frontiers in Global Women's Health, 2022)
Introduction: In Senegal, discontinuation due to sides effects of long-acting, reversible contraceptives (LARCs) is relatively low; 5% of new implant acceptors and 11% of new IUD acceptors stop using in their first year because of health or side effect concerns. This study investigated factors associated with LARC discontinuation in the first 12 months of use in Senegal and explored how LARC users cope with side effects. Methods: This mixed-method study involved quantitative interviews at five time points with LARC acceptors recruited from three service channels between February 2018 and March 2019. Qualitative interviews were conducted in August 2018 with a subset of those who experienced side effects. Logistic regression models identified factors associated with discontinuation due to side effects and discontinuation for any reason. Twelve-month discontinuation rates due to side effects were also estimated using a cumulative incidence function (CIF) approach to account for time to discontinuation. Results: In logistic models, method choice (IUD or implant) [OR=3.15 (95% CI: 1.91-5.22)] and parity [OR=0.81 (95% CI: 0.7-0.94)] were associated with discontinuation due to side effects; IUD users and women with fewer children were more likely to discontinue. Results for all-cause discontinuation were similar: method choice [OR=2.39 (95% CI:1.6-3.58)] and parity [OR=0.86 (95% CI: 0.77-0.96)] were significant predictors. The 12-month side effect CIF discontinuation rate was 11.2% (95% CI: 7.9%-15.0%) for IUDs and 4.9% (95% CI: 3.5%-6.6%) for implants. Side effect experiences varied, but most women considered menstrual changes the least acceptable. No statistically significant differences across services channels were observed. Conclusions: In this study in Senegal, the choice between implants and IUDs had a significant impact on continuation, and women with more children continued LARC methods longer, despite side effects.